The Accuracy and Reliability of Visually Assessed Pharyngeal Opening Pressures During Drug‐Induced Sleep Endoscopy. (29th January 2023) - Yu, Jason L.; Thuler, Eric; Seay, Everett G.; Schwartz, Alan R.; Dedhia, Raj C.
Abstract: Objective: To examine the accuracy and interrater reliability of a visually assessed vs airflow‐based measure of pharyngeal collapsibility obtained in patients with obstructive sleep apnea undergoing drug‐induced sleep endoscopy (DISE). Study Design: Prospective observational study. Setting: Academic tertiary care practice. Methods: Patients underwent DISE with airflow monitoring and nasal positive airway pressure titration to determine visual and airflow‐based levels of pharyngeal opening pressure (PhOP). Visual DISE‐PhOP was assessed by 2 blinded independent raters and defined as the pressure at which visual confirmation of airway collapse, including snoring, was abolished. Airflow‐based DISE‐PhOP was defined as the minimally effective positive airway pressure that abolished inspiratory flow limitation. Equivalence testing between visual and airflow DISE‐PhOP of each rater was performed with the two one sided T‐test (TOST) with an a priori equivalence bound of ±1 cm H2 O. Interrater reliability was evaluated with the intraclass correlation coefficient. Results: One hundred patients were enrolled in the study and 77 completed the full evaluation. The population was predominantly male (74%) with an average age of 54.8 years, body mass index of 30.1 kg/m 2, and apnea‐hypopnea index of 30.7 events/h. Equivalence testing showed that both raters were within ±1 cm H2 O of airflow‐based DISE‐PhOP (−0.43 to 0.09 cm H2 O and −0.32 to 0.48 cm H2 O). Interrater reliability of visual DISE‐PhOP between the raters was also good to excellent with an intraclass correlation coefficient of 0.895 (95% CI, 0.84‐0.932). Conclusion: DISE‐PhOP, a measure of upper airway collapsibility, was equivalent between airflow‐based and visual assessments with strong interrater reliability, supporting its adoption as a standardized objective parameter in clinical DISE.